Antifungal activity and gene expression of lipopeptide antibiotics in strains of genus Bacillus - Grabova, A.Yu.; Dragovoz, I.V.; Zelena, L.B.; Tkachuk, D.M.; Avdeeva, L.V. (Вiopolymers and Cell, 2016)
Aim. To research the antifungal activity and gene expression of lipopeptide antibiotics in strains of genus Bacillus. Methods. Deferred antagonism method, PCR, qRT-PCR, MALDI-TOF mass spectrometry. Results. It was revealed that Bacillus sp. strains C6 and Lg37s out of five tested strains had the highest antifungal activity. Based on the molecular genetic methods, it was shown that the expression of genes of lipopeptide antibiotics, related to the fengycin family, occurred in all these strains. At the same time, the gene expression of cyclolipopeptide iturin was found in the Bacillus sp. strains C6 and Lg37s. It was determined that Bacillus sp. C6 strain had the highest level of expression of the fengycin operon`s genes, whereas the lowest level was observed in Bacillus sp. C10 strain. By means of MALDI-TOF mass spectrometry, the presence of fengycins in the cell-free cultural fluid of Bacillus sp. C6 strain was detected. Conclusion. The direct correlation between the level of antifungal activity and the fengycin synthetases expression has not been disclosed. A higher level of antagonism detected for two Bacillus strains is more likely associated with the expression and subsequent synthesis of fengycin and iturin. Мета. Дослідити протигрибкову активність та експресію генів ліпопептідних антибіотиків у штамів бактерій роду Bacillus. Методи. Метод відстроченого антагонізму, PCR, qRT-PCR, MALDI-TOF мас-спектрометрія. Результати. З п'яти досліджених штамів найбільшу протигрибкову активністю показали штами Bacillus sp. С6 і Lg37s. Визначено, що у всіх штамів відбувається експресія генів ліпопептідних антибіотиків сімейства фенгіцінов. Для штамів Bacillus sp. С6 і Lg37s показана експресія гену синтезу ціклоліпопептіда ітуріна, найбільш активно експресуються гени фенгіцінового оперона у штаму Bacillus sp. С 6, найменш – у Bacillus sp. С 10. За допомогою MALDI-TOF масспектрометрії виявлено наявність фенгіцінов в безклітинній культуральній рідини штаму Bacillus sp. С6. Висновки. Прямої залежності між рівнем протигрибкової активності і експресією фенгіцінсінтетаз не виявлено. Більш високий рівень антагонізму, виявлений у двох штамів бацил, ймовірно, пов'язаний з експресією генів та подальшим синтезом фенгіціну та ітуріну. Цель. Исследовать противогрибковую активность и экспрессию генов липопептидных антибиотиков у штаммов бактерий рода Bacillus. Методы. Метод отсроченного антагонизма, PCR, qRT-PCR, MALDI-TOF масс-спектрометрия. Результаты. Из пяти исследованных штаммов наибольшей противогрибковой активностью обладают штаммы Bacillus sp. С6 и Lg37s. Показано, что у всех штаммов происходит экспрессия генов липопептидных антибиотиков семейства фенгицинов. Для штаммов Bacillus sp. С6 и Lg37s показана экспрессия гена циклолипопептида итурина, наиболее активно экспрессируются гены фенгицинового оперона у штамма Bacillus sp. С6, наименее – у Bacillus sp. С10. С помощью MALDI-TOF масс-спектрометрии обнаружено наличие фенгицинов в бесклеточной культуральной жидкости штамма Bacillus sp. С 6. Выводы. Прямой зависимости между уровнем противогрибковой активности и экспрессией фенгицинсинтетаз не установлено. Более высокий уровень антагонизма, обнаруженный у двух штаммов бацилл, вероятно, связан с экспрессией и дальнейшим синтезом фенгицина и итурина.